English

If X Sin 45° Cos2 60° = Tan 2 60 ∘ C O S E C 30 ∘ Sec 45 ∘ Cot 2 ∘ 30 ∘ , Then X = - Mathematics

Advertisements
Advertisements

Question

If x sin 45° cos2 60° = \[\frac{\tan^2 60^\circ cosec30^\circ}{\sec45^\circ \cot^{2^\circ} 30^\circ}\], then x =

 

Options

  • 2

  • 4

  • 8

  • 16

MCQ

Solution

8
We have: 
\[x \sin 45^\circ\cos^2 60^\circ = \frac{\tan^2 60^\circ cosec 30^\circ}{\sec45^\circ \cot^2 30^\circ}\]

\[ \Rightarrow x \times \left( \frac{1}{\sqrt{2}} \right) \times \left( \frac{1}{2} \right)^2 = \frac{\left( \sqrt{3} \right)^2 \times \left( 2 \right)}{\left( \sqrt{2} \right) \times \left( \sqrt{3} \right)^2}\]

\[ \Rightarrow \frac{x}{4\sqrt{2}} = \frac{6}{3\sqrt{2}}\]

\[ \Rightarrow x = \frac{6}{3\sqrt{2}} \times 4\sqrt{2}\]

\[ \Rightarrow x = 8\]

shaalaa.com
  Is there an error in this question or solution?
Chapter 5: Trigonometric Functions - Exercise 5.5 [Page 42]

APPEARS IN

RD Sharma Mathematics [English] Class 11
Chapter 5 Trigonometric Functions
Exercise 5.5 | Q 19 | Page 42

Video TutorialsVIEW ALL [1]

RELATED QUESTIONS

Find the principal and general solutions of the equation  `cot x = -sqrt3`


Find the general solution of the equation cos 4 x = cos 2 x


Find the general solution of the equation cos 3x + cos x – cos 2x = 0


Find the general solution for each of the following equations sec2 2x = 1– tan 2x


Find the general solution of the equation  sin x + sin 3x + sin 5x = 0


If \[x = \frac{2 \sin x}{1 + \cos x + \sin x}\], then prove that

\[\frac{1 - \cos x + \sin x}{1 + \sin x}\] is also equal to a.

If \[a = \sec x - \tan x \text{ and }b = cosec x + \cot x\], then shown that  \[ab + a - b + 1 = 0\]


If \[T_n = \sin^n x + \cos^n x\], prove that  \[2 T_6 - 3 T_4 + 1 = 0\]


Prove that:  tan 225° cot 405° + tan 765° cot 675° = 0


Prove that:

\[3\sin\frac{\pi}{6}\sec\frac{\pi}{3} - 4\sin\frac{5\pi}{6}\cot\frac{\pi}{4} = 1\]

 


Prove that

\[\left\{ 1 + \cot x - \sec\left( \frac{\pi}{2} + x \right) \right\}\left\{ 1 + \cot x + \sec\left( \frac{\pi}{2} + x \right) \right\} = 2\cot x\]

 


Prove that:
\[\sin\frac{13\pi}{3}\sin\frac{8\pi}{3} + \cos\frac{2\pi}{3}\sin\frac{5\pi}{6} = \frac{1}{2}\]


Prove that:
\[\sin \frac{13\pi}{3}\sin\frac{2\pi}{3} + \cos\frac{4\pi}{3}\sin\frac{13\pi}{6} = \frac{1}{2}\]


If \[\frac{3\pi}{4} < \alpha < \pi, \text{ then }\sqrt{2\cot \alpha + \frac{1}{\sin^2 \alpha}}\] is equal to


If x is an acute angle and \[\tan x = \frac{1}{\sqrt{7}}\], then the value of \[\frac{{cosec}^2 x - \sec^2 x}{{cosec}^2 x + \sec^2 x}\] is


sin2 π/18 + sin2 π/9 + sin2 7π/18 + sin2 4π/9 =


If tan A + cot A = 4, then tan4 A + cot4 A is equal to


If sec x + tan x = k, cos x =


If \[f\left( x \right) = \cos^2 x + \sec^2 x\], then


Find the general solution of the following equation:

\[\sqrt{3} \sec x = 2\]

Solve the following equation:

\[3 \cos^2 x - 2\sqrt{3} \sin x \cos x - 3 \sin^2 x = 0\]

Solve the following equation:

\[\sin x + \sin 2x + \sin 3 = 0\]

Solve the following equation:

\[\sin x + \sin 2x + \sin 3x + \sin 4x = 0\]

Solve the following equation:

\[\sin 3x - \sin x = 4 \cos^2 x - 2\]

Solve the following equation:

\[\sin 2x - \sin 4x + \sin 6x = 0\]

Solve the following equation:

\[\tan x + \tan 2x + \tan 3x = 0\]

Solve the following equation:

`cosec  x = 1 + cot x`


Write the values of x in [0, π] for which \[\sin 2x, \frac{1}{2}\]

 and cos 2x are in A.P.


Write the number of values of x in [0, 2π] that satisfy the equation \[\sin x - \cos x = \frac{1}{4}\].


In (0, π), the number of solutions of the equation ​ \[\tan x + \tan 2x + \tan 3x = \tan x \tan 2x \tan 3x\] is 


If \[e^{\sin x} - e^{- \sin x} - 4 = 0\], then x =


If \[\sqrt{3} \cos x + \sin x = \sqrt{2}\] , then general value of x is


General solution of \[\tan 5 x = \cot 2 x\] is


Solve the following equations:
cos 2θ = `(sqrt(5) + 1)/4`


Choose the correct alternative:
If tan 40° = λ, then `(tan 140^circ - tan 130^circ)/(1 + tan 140^circ *  tan 130^circ)` =


Choose the correct alternative:
If sin α + cos α = b, then sin 2α is equal to


If sin θ and cos θ are the roots of the equation ax2 – bx + c = 0, then a, b and c satisfy the relation ______.


Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×